The music of life in Galway Kinnell's poetry - Leong, Jia En (Nanyang Technological University, 2021)
In Galway Kinnell’s poetry, the musicality of words is central to his artistic process of shaping poetic form. In many of his poems, various soundful dictions and poetic devices are utilised to enhance the rhythm of the piece which in turn generate deep engagement with topics such as love and mortality. Many critics of Kinnell’s poetry have identified the inherent musicality in his words. However, there is a lack of in-depth critical examination on the musicality in his works. Therefore, I propose that listening to the sounds and prosodies of his poems offers a valuable critical approach to his work. To effectively read Kinnell it is imperative that one be alert to the music of his pauses and words, listening to them as though the poems are pieces of music. However, this method of musical analysis will not simply be used to pigeonhole his poems into a mere narrative analysis of comparing music theory and tagging musical devices onto his poetic form. I will instead be looking at the synthesis between form and content as I analyse his poems, showing not just the musicality but also how it transpires in its production of meaning. Every theorist will read a poem’s sounds differently due to the variety of cultural and linguistic backgrounds which influences each individual’s reading of the poem. This affects the objectivity of the interpretation of the poem, rendering it a subjective experience for each reader. However, I will prove that Kinnell himself does underscore the importance of music and consciously leans towards musicality in his craft. Hence, hearing the musical patterns within his poetry will not merely be my own subjective interpretation of the sounds within it. I will demonstrate that musicality traverses all of his poems, embracing each and every aspect of his changes in poetic form, imagery, or way of speaking throughout the entirety of his career as a poet.